Timing of Antenatal Steroid Administration and Effects on the Newborn Infant: A Retrospective Study - Taleghani, Afshin A.; Bhriguvanshi, Arpita; Kamath-Rayne, Beena D.; Liu, Chunyan; Narendran, Vivek (American Journal of Perinatology, 2020)
Objective The timing of antenatal steroids (ANS) on short- and long-term effects on newborn infants was evaluated.Study Design This study was conducted at the University of Cincinnati Medical Center Level-III Neonatal Intensive Care Unit by reviewing the medical records of all women with history of ANS exposure from January 2015 to December 2018. We compared outcomes of newborns delivered within the ideal therapeutic window of 24 hours to 7 days (within window [WW]) after administration to those exposed and delivered outside the therapeutic window (outside window primary group [OWP]). Outcomes included anthropometrics, blood sugars, thyroid hormone profile, and neonatal morbidities.Results A total of 669 patients were identified as having received at least two doses of ANS. Two-thirds of them delivered within the ideal therapeutic window. Significant differences were found in anthroprometrics including lower birth weight, shorter length, and smaller head circumferences in those born within the window compared with those outside the window. Derangements in glucose homeostasis requiring treatment and elevations of thyroid stimulating hormone (TSH) were seen in infants born outside the ideal therapeutic window compared with those born within the therapeutic window. No differences were found in neonatal morbidities including severe intraventricular hemorrhage (sIVH), necrotizing enterocolitis (NEC), need for resuscitation, exogenous surfactant administration, continuous positive airway pressure (CPAP), mechanical ventilation, bronchopulmonary dysplasia (BPD), or periventricular leukomalacia (PVL). After controlling for selected covariates, only birth length was different between the groups.Conclusion Effects on anthropometrics, glucose homeostasis, and thyroid function support the need to develop new or refine existing risk stratification systems to time the administration of antenatal steroids. Better targeting of women and fetuses may confer the benefits of systemic corticosteroids while mitigating the risks of adverse effects.Key Points
Keywords: antenatal steroids; respiratory distress syndrome; intraventricular hemorrhage; newborn screening; neonatal hypoglycemia